2010
DOI: 10.1556/ceugeol.53.2010.2-3.8
|View full text |Cite
|
Sign up to set email alerts
|

First record ofRhabdoceras suessi(Ammonoidea, Late Triassic) from the Transylvanian Triassic Series of the Eastern Carpathians (Romania) and a review of its biochronology, paleobiogeography and paleoecology

Abstract: The occurrence of the heteromorphic ammonoid Rhabdoceras suessi Hauer, 1860, is recorded for the first time in the Upper Triassic limestone of the Timon-Ciungi olistolith in the Raràu Syncline, Eastern Carpathians. A single specimen of Rhabdoceras suessi co-occurs with Monotis (Monotis) salinaria that constrains its occurrence here to the Upper Norian (Sevatian 1). It is the only known heteromorphic ammonoid in the Upper Triassic of the Romanian Carpathians. Rhabdoceras suessi is a cosmopolitan species widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Mirăuţă et al (1993 reported rich foraminiferal and ostracod assemblages indicative of a late Norian age. In other outcrops, situated in the Muchea Verde area, near the Poşta village, the presence of the ammonoid Sagenites quinquepunctatus Mojsisovics, 1873Mojsisovics, -1902, together with bivalves of Monotis (Monotis) salinaria-haueri Kittl, 1912 group, is diagnostic for the Sagenites quinquepunctatus Zone of the upper Norian, which corresponds to the lower Sevatian (= Sevatian 1) (Krystyn 2008;Grădinaru & Sobolev 2010). Samples Frecăţei A1-2 and B come from this part of the log.…”
Section: Detail Descriptions Of Fossiliferous Logsmentioning
confidence: 99%
“…Mirăuţă et al (1993 reported rich foraminiferal and ostracod assemblages indicative of a late Norian age. In other outcrops, situated in the Muchea Verde area, near the Poşta village, the presence of the ammonoid Sagenites quinquepunctatus Mojsisovics, 1873Mojsisovics, -1902, together with bivalves of Monotis (Monotis) salinaria-haueri Kittl, 1912 group, is diagnostic for the Sagenites quinquepunctatus Zone of the upper Norian, which corresponds to the lower Sevatian (= Sevatian 1) (Krystyn 2008;Grădinaru & Sobolev 2010). Samples Frecăţei A1-2 and B come from this part of the log.…”
Section: Detail Descriptions Of Fossiliferous Logsmentioning
confidence: 99%
“…With regard to Far East Russia, it is to be noted that most of the regions where timorensis occurrences have been reported, although many of them are doubtful and not properly dated by ammonoid biostratigraphy, are in allochthonous terranes (Nokleberg et al, 1994;Vishnevskaya & Filatova, 1994;Parfenov et al, 2009), which during the Triassic were positioned in low-latitudes in the eastern Panthalassa (Fig. 4/21-24), as documented by the occurrence of Monotis bivalves, conodonts, radiolarians, and of Rhabdoceras ammonoids (Chekhov, 1982;Dagys et al, 1983;Bragin, 1991;Klets, 2008;Grădinaru & Sobolev, 2010). Liu K et al (2021), based on detrital zircon U-Pb data and also on geochronological data, argued that in Sikhote-Alin different sedimentary rocks were juxtaposed by syn-and post-subduction sinistral displacements along the NE Asian continental margin during the late Mesozoic.…”
Section: Chiosella Timorensis a Conodont Species Without A Cosmopolitan Occurrencementioning
confidence: 99%